سماجی ترقی کے لیے معاشی وسائل و ذرائع کا پائیدار استعمال: اسلامی تعلیمات کی روشنی میں علمی جائزہ: Sustainable Utilization of Economic Resources for Social Development: An Academic Review in the Light of Islamic Teachings - Shahr Bano; Dr. Sajila Kausar (Al-Amīr Research Journal for Islamic Studies, 2025)
This study explores the Islamic conception of a welfare society as a distinctive and comprehensive model rooted in divine guidance and human responsibility. Islamic teachings prioritize social justice, public welfare, and the collective good, establishing a framework in which human beings, as God’s vicegerents, are entrusted with moral agency and stewardship over the material resources of the earth and sky. The Qur’anic notion of external and internal blessings underscores the obligation to utilize these resources responsibly, maintain balance, and uphold justice in all socio-economic affairs. Within the Islamic welfare system, sustainable development is defined not only as material progress but also as the advancement of human well-being and equitable resource distribution according to individual effort. Islamic teachings present development as a holistic process encompassing moral, spiritual, and economic dimensions. The Qur’an and Sunnah devote considerable attention to economic matters—including inheritance, zakat, charity, and financial transactions—highlighting the centrality of livelihood and economic justice in Islamic social organization. The economic principles established by the Prophet Muhammad (peace be upon him) fostered a just and stable society, offering an ethical framework unmatched by other socio-economic systems. This research synthesizes Qur’anic and Prophetic teachings related to welfare, resource management, and development, while also examining historical illustrations of these principles throughout Islamic civilization. A narrative and analytical methodology is employed to contextualize the Islamic welfare model within broader academic discussions on justice, development, and social order. Keywords: Islamic welfare system; social justice; sustainable development; resource stewardship; Qur’anic economic principles; Prophetic teachings.